Tumour necrosis factor inhibition versus rituximab for patients with rheumatoid arthritis who require biological treatment (ORBIT): an open-label, randomised controlled, non-inferiority, trial. Issue 10041 (16th July 2016) - Porter, Duncan; van Melckebeke, Jurgen; Dale, James; Messow, C Martina; McConnachie, Alexander; Walker, Andrew; Munro, Robin; McLaren, John; McRorie, Euan; Packham, Jon; Buckley, Christopher D; Harvie, John; et al.
Summary: Background: Tumour necrosis factor (TNF) inhibition and B-cell depletion are highly effective treatments for active rheumatoid arthritis, but so far no randomised controlled trials have directly compared their safety, efficacy, and cost-effectiveness. This study was done to test the hypothesis that using rituximab would be clinically non-inferior and cheaper compared with TNF inhibitor treatment in biological-treatment naive patients with rheumatoid arthritis. Methods: This open-label, randomised controlled, non-inferiority trial enrolled patients with active, seropositive rheumatoid arthritis and an inadequate response to synthetic disease modifying anti-rheumatic drugs (DMARDs) from 35 rheumatology departments in the UK. Patients were randomly assigned 1:1 to the rituximab or TNF inhibitor groups with minimisation to account for methotrexate intolerance using a web-based randomisation system. Patients were given intravenous rituximab 1 g on days 1 and 15, and after 26 weeks if they responded to treatment but had persistent disease activity (28 joint count disease activity score [DAS28-ESR] >3·2; rituximab group) or a TNF inhibitor—adalimumab (40 mg subcutaneously every other week) or etanercept (50 mg per week subcutaneously) according to the patient's and rheumatologist's choice (TNF inhibitor group). Patients could switch treatment in the case of drug-related toxic effects or absence or loss of response. The primary outcome measure was the change in DAS28-ESR between 0 and 12 months in the per-protocol population of patients who were assigned to treatment and remained in follow-up to 1 year. We assessed safety in all patients who received at least one dose of study drug. We also assessed the cost-effectiveness of each strategy. The non-inferiority margin was specified as 0·6 DAS28-ESR units. This study is registered withClinicalTrials.gov, numberNCT01021735 . Findings: Between April 6, 2009, and Nov 11, 2013, 295 patients were randomly assigned and given either rituximab (n=144) or TNF inhibitor (n=151) treatment. After 12 months, the change in DAS28-ESR for patients assigned to rituximab was −2·6 (SD 1·4) and TNF inhibitor was −2·4 (SD 1·5), with a difference within the prespecified non-inferiority margin of −0·19 (95% CI −0·51 to 0·13; p=0·24). The health-related costs associated with the rituximab strategy were lower than the TNF inhibitor strategy (£9405 vs £11 523 per patient, p<0·0001). 137 (95%) of 144 patients in the rituximab group and 143 (95%) of 151 patients in the TNF inhibitor group had adverse events. 37 serious adverse events occurred in patients receiving rituximab compared with 26 in patients receiving TNF inhibitors, of which 27 were deemed to be possibly, probably, or definitely related to the treatment (15 vs 12, p=0·5462). One patient in each group died during the study. Interpretation: Initial treatment with rituximab is non-inferior to initial TNF inhibitor treatment in patients seropositive for rheumatoid arthritis and naive to treatment with biologicals, and is cost saving over 12 months. Funding: Arthritis Research UK, Roche.